2016
DOI: 10.1007/s00464-015-4720-x
|View full text |Cite
|
Sign up to set email alerts
|

A single-center experience with the laparoscopic Warshaw technique in 122 consecutive patients

Abstract: Background Preservation of the spleen in distal pancreatectomy has recently attracted considerable attention. Our current study aimed in the first instance to define the safety of lap-WT in relation to the capacity of this technique to achieve preservation of the spleen and secondly to investigate the effectiveness of a planned lap-WT procedure or early conversion to lap-WT in selected patients with a large tumor attached to the splenic vessels.MethodsAmong 1056 patients who underwent a laparoscopic distal pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 19 publications
2
32
0
1
Order By: Relevance
“…Kim et al. reported 54.2% (66/122) of patients suffered some degree of splenic infarction after LWT; however, splenic perfusion returned to normal in most patients and none required splenectomy. Zhou et al.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al. reported 54.2% (66/122) of patients suffered some degree of splenic infarction after LWT; however, splenic perfusion returned to normal in most patients and none required splenectomy. Zhou et al.…”
Section: Discussionmentioning
confidence: 99%
“…No bleeding event occurred in these patients with varices. The formation of gastric/perigastric varices might be regarded as a para‐physiological phenomenon after interruption of the main splenic vessels, and it is therefore not associated with gastrointestinal bleeding during long‐term follow‐up . Spleen infarction did also occur in 8 (24%) patients with our robotic approach, and no adverse clinical consequence such as infarction‐related spleen abscess was observed.…”
Section: Discussionmentioning
confidence: 79%
“…Spleen infarction and gastric varices are two concerns after distal pancreatectomy with spleen preservation by the Warshaw technique. The rate of spleen infarction was reported to be 2%–74.3%, the rate of gastric varices 8.1%–52.5% and the rate of perigastric varices 25%–70% . However, they are usually asymptomatic during the post‐operative follow‐up period .…”
Section: Discussionmentioning
confidence: 99%
“…Warshaw group have reported that none of 158 patients who underwent the Warshaw operation developed GI bleeding and only 3 (1.9%) patients required a reoperation because of splenic infarction during a follow-up period of up to 21 years [4]. Kim et al also have reported no clinical significant splenic infarctions or gastric varices in any case after the Warshaw operation [10]. In our center, we performed 19 cases of laparoscopic Warshaw operation from 2014.…”
Section: Discussionmentioning
confidence: 98%